Pemodelan Dinamik Robot Enam Derajat Kebebasan - Syachril Fauzie (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
Precise controlling at one particular high-speed manipulator require realisticdynamics model from an arm (end effector). Used approach here is to pass simulationmodeling made in a few function by using approach of equations pursuant to co-ordinateconcept, style and Force. Where from this equation will be obtained the level of torsi at eachjoint which depend on inertia of manipulator, gravitation, friction, style of corolois and iscentrifugal. Maximal values and minimum values from every this equation is later expectedcan useful in designing mechanical structure and controller.Keywords: lagrange-euler, corolois, torque, joint.